Formulation of instant porridge based on moringa leaves as a functional food for nursing mother. (May 2019) - Pranowo, D; Mustaniroh, S A; Ihwah, A
Abstract: Female workers reach 43.3 million people nowadays, which 25 million are in the reproductive age. Based on Basic Health Research, the number of nursing mothers only 42% far below the target of 80%. This study is to make instant porridge formulations for nursing mothers. The materials are Moringa leaves, soy flour, banana flour, oats, palm sugar and skim milk. This research was arranged using Linear Programming Solver 1.9.4 to determine the best formulation based on nutritional adequacy rate for nursing mothers and hedonic test to determine the level of consumer preference for the product. The optimal porridge formulation is 5 grams Moringa leaves powder, 5 grams of soy flour, 20 grams of banana flour, 25 grams of oat, 22.5 grams of palm sugar and 22.5 grams of skim milk. The hedonic test is carried out on nursing women and productive age in the area of Temas, Batu, Malang Regency with the results of taste, colour, appearance and average texture worth four which means they like the product.